Never too late to try something new: attitudes and intention to taste foods from alternative protein sources in a sample of Italian older adults - Vanutelli, Maria Elide; Adorni, Roberta; Leone, Paolo Alberto; Luperini, Aldo; D’Addario, Marco; Steca, Patrizia (Frontiers in Nutrition, 2025)
IntroductionNutrition in older adults requires special attention due to protein-energy malnutrition (PEM) risk. Therefore, identifying healthy and sustainable protein sources is crucial, as traditional animal proteins pose challenges to both health and the environment. While most research focuses on younger populations, this study examined the responses of older adults to three alternative protein sources (APS): one plant-based (PBF) and two animal-based sources: cultured meat (CM) and insect-based foods (IBF). We investigated the role of explicit and automatic attitudes in shaping intention to consume (ITC) and the influence of familiarity.MethodsA between-subjects design was performed: Each participant was randomly assigned to one APS, reported explicit attitudes and ITC, and completed an Implicit Association Test (IAT) to assess automatic attitudes.ResultsRegression analyses showed that ITC varied across APS. For PBF, familiarity was the strongest predictor, followed by explicit attitudes related to taste and automatic attitudes. For CM, ITC was primarily associated with explicit attitudes concerning both taste and safety. For IBF, ICT was mainly related to explicit attitudes concerning taste. ANOVAs comparing the three APSs revealed that IBF was the least favored option. Unexpectedly, although PBF was rated as tastier and safer than CM, it was less preferred in terms of automatic attitudes and ITC.DiscussionThese findings offer new insights into older adults’ openness to APS. Disgust and perceived risk were identified as the primary factors influencing the acceptance of animal-based APS, while familiarity and automatic reactions were key factors in the acceptance of PBF. Importantly, although PBF received positive evaluations at the explicit level, it prompted negative automatic attitudes and low intention to consume, suggesting that older adults may implicitly resist PBF, viewing it as less compatible with their dietary habits compared to CM. This evidence challenges the common belief that PBF is the most accepted category of APS and highlights the need to investigate further the implicit barriers that may prevent the integration of these foods for healthy aging.